The Online First-Year Experience: Defining and Illustrating a New Reality. Issue 3 (August 2020) - Korstange, Ryan; Hall, Jeff; Holcomb, Jamie; Jackson, Jasmeial
All incoming students have a first experience with their institution. This article reviews literature on adult education, online learning, and first-year student success to articulate the scope of experiences and programs that ought to be included in institutional efforts aimed at helping adult students be successful in their first year of online education. In addition, three approaches to support these online students in their first year of college are illustrated. Key areas surveyed are online orientation programs, online first-year experience courses, and the co-curricular engagement of online learners. Examination of these cases demonstrates that supporting online first-year students is quite important, particularly given the proliferation of online students and their lag in standard measures of success.